Decision Support System (DSS) Determining Credit Customer Pada PT. Bank Rakyat Indonesia (Persero) Tbk - Fikry, Muhamamd (Jurnal EDik Informatika, 2014)
Computer as one advance sintechnology can help people to improve the quality and quantity of work, as well ashelp in getting the information and decision-making to decision making. The concept of decision support systems (decision support system) is one branch of artificial intelligence (artificial intelligence) that is widely used to help makea decision. Many methods can beapplied to decision support system to help providea solutioninaproblemalternaif. One such methodis a method ofdata cleaningand datatransformation. This method will help to process in complete data into acomplete data, then transform the data using theme thods of data transformation.Keywords: decision support system, data cleaning, data transformasi, determining credit